Conversion of Glycogen Phosphorylase b to a by Non-Activated Phosphorylase b Kinase: an In Vitro Model of the Mechanism of Increase in Phosphorylase a Activity with Muscle Contraction - Villar-Palasi, C. (1970)
Phosphorylase b kinase activity, as present in resting muscle in the non-activated form, appears to be ample to account for the fast appearance of phosphorylase a observed with muscle contraction. The kinase activity is repressed by free ATP and stimulated by free Mg(2+). Phosphorylase b kinase activity increases greatly when the Mg(2+):ATP ration exceeds 1. It is proposed that the breakdown of ATP that occurs during muscle contraction may represent the triggering factor for the observed in vivo conversion of phosphorylase b into a.